A pesticide paradox: fungicides indirectly increase fungal infections. Issue 8 (29th September 2017) - Rohr, Jason R.; Brown, Jenise; Battaglin, William A.; McMahon, Taegan A.; Relyea, Rick A.
Abstract: There are many examples where the use of chemicals have had profound unintended consequences, such as fertilizers reducing crop yields (paradox of enrichment) and insecticides increasing insect pests (by reducing natural biocontrol). Recently, the application of agrochemicals, such as agricultural disinfectants and fungicides, has been explored as an approach to curb the pathogenic fungus, Batrachochytrium dendrobatidis ( Bd ), which is associated with worldwide amphibian declines. However, the long‐term, net effects of early‐life exposure to these chemicals on amphibian disease risk have not been thoroughly investigated. Using a combination of laboratory experiments and analysis of data from the literature, we explored the effects of fungicide exposure on Bd infections in two frog species. Extremely low concentrations of the fungicides azoxystrobin, chlorothalonil, and mancozeb were directly toxic to Bd in culture. However, estimated environmental concentrations of the fungicides did not reduce Bd on Cuban tree frog ( Osteopilus septentrionalis ) tadpoles exposed simultaneously to any of these fungicides and Bd, and fungicide exposure actually increased Bd ‐induced mortality. Additionally, exposure to any of these fungicides as tadpoles resulted in higher Bd abundance and greater Bd ‐induced mortality when challenged with Bd post‐metamorphosis, an average of 71 d after their last fungicide exposure. Analysis of data from the literature revealed that previous exposure to the fungicide itraconazole, which is commonly used to clear Bd infections, made the critically endangered booroolong frog ( Litoria booroolongensis ) more susceptible to Bd . Finally, a field survey revealed that Bd prevalence was positively associated with concentrations of fungicides in ponds. Although fungicides show promise for controlling Bd, these results suggest that, if fungicides do not completely eliminate Bd or if Bd recolonizes,  exposure to fungicides has the potential to do more harm than good. To ensure that fungicide applications have the intended consequence of curbing amphibian declines, researchers must identify which fungicides do not compromise the pathogen resistance mechanisms of amphibians.